DISORDERS OF THE AUTONOMIC NERVOUS SYSTEM IN THE CARDIOLOGY PRACTICE: FOCUS ON THE ANALYSIS OF HEART RATE VARIABILITY - E. B. Akhmedova; B. U. Mardanov; M. N. Mamedov (Столичная издательская компания, 2015)
Heart rate variability (HRV) in patients with ischemic heart disease, a life-threatening heart rhythm disorders, as well as diabetes mellitus (DM) is considered. A significant association between the autonomic regulation of the cardiovascular system and death from cardiovascular causes is identified. The reactions of the autonomic nervous system (ANS) can serve as a precipitating factor of arrhythmias in patients with heart disorders. Analysis of HRV at rest is the main and informative method for determination of the ANS disorders. HRV decreases greatly in patients with acute myocardial infarction, cardiac arrhythmia, and DM, predicting a high risk of death. The leading cause of death in diabetic patients is cardiac autonomic neuropathy, with the development of "silent" ischemia and painless myocardial infarction. Autonomic regulation of the heart rate should be assessed for early diagnosis and prevention of complications in the form of sudden death.